Consumer Nostalgia Literature Review and an Alternative Measurement Perspective - Gineikienė, Justina (Organizations and Markets in Emerging Economies, 2013)
During the last two decades consumer nostalgia literature has experienced the growing amount of research, nonetheless, the nomological network in the area is still poorly established and fundamental questions of generalizability and measurement of nostalgia effects remain unanswered. This paper represents an attempt to comprehensively assess extant research in consumer nostalgia field, distinguish developments in the literature by summarizing the main findings of previous research and establishing theoretical trends. The analysis reveals that a number of demographic, social and psychological nostalgia antecedents, moderators and outcomes remain at the propositions level or lack the accumulated empirical quantitative support and validation from other studies. Therefore, specific recommendations regarding the development of nostalgia nomological network are provided to aid the continued theoretical and methodological improvements in the area. Since 1991 research in nostalgia has assumed that the correct measurement approach is a reflective one. This paper offers an alternative perspective for viewing and operationalizing nostalgia construct as a formative construct. Guidelines are summarized that aim to assist researchers with decision rules on whether to employ formative or reflective nostalgia measurement for future research. One of the main contributions of this study is to show the need for researchers to explicitly justify their choice of reflective or formative measurement models by supporting it with theoretical arguments and empirical evidence.